Antistatic PE film masterbatch and preparation method thereof
By using nano zinc oxide aluminum particles and carbon black in color masterbatches, combined with ultrasonic oscillation and extrusion processes, the problem of insufficient antistatic effect and thermal stability of color masterbatches is solved, and high-performance resistance is achieved Electrostatic PE film masterbatch.
Patent Information
- Application Number
- CN202311200224.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-18
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-09-18
AI Technical Summary
The existing masterbatches have shortcomings in antistatic effects and thermal stability, which affect their applicability and performance during processing.
Using a combination of PE carrier resin, antistatic agent, titanium dioxide, carbon black and zinc stearate, the synergistic action of nano zinc oxide aluminum particles combined with ultrasonic oscillation and extrusion processes to improve the conductivity and resistance of color masterbatches. Electrostatic properties.
It significantly improves the antistatic properties and thermal stability of the masterbatch, enhances its mechanical properties and dispersion, and solves the problems of high temperature stability and weather resistance chromatic aberration caused by traditional antistatic materials.
Smart Images

Figure BDA0004453793150000061 
Figure BDA0004453793150000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of masterbatches, and in particular relates to an antistatic PE film masterbatch and a preparation method thereof. Background Art
[0002] The full name of masterbatch is masterbatch, also called color seed. It is a new type of colorant for polymer materials, also called pigment preparation. Masterbatch is mainly used on plastics. Masterbatch is composed of three basic elements: pigment, carrier and additive, that is, pigment + carrier + additive = masterbatch. It is an aggregate obtained by uniformly attaching an extraordinary amount of pigment to the resin, which can be called pigment concentrate (Pigment Concentration), so its coloring power is higher than the pigment itself. When processing, a small amount of masterbatch is mixed with uncolored resin to achieve the coloring resin or product with the designed pigment concentration. Masterbatch coloring is the most commonly used plastic coloring method today.
[0003] The external structure of general masterbatches is relatively uniform, but the masterbatch itself does not have anti-static ability, which greatly affects the use effect of the masterbatch, reduces the applicability of the masterbatch in daily processing, and cannot meet people's use needs well. In view of the above situation, technical innovation is carried out on the basis of the existing masterbatch.
[0004] At present, the methods of adding antistatic agents are generally divided into external surface treatment method and internal addition method. The internal addition method is to add antistatic agents or conductive fillers into the resin to achieve the antistatic effect. For example, the invention patent with patent application number 2011025089.0 published "An antistatic polyester film and preparation method" mixes organic nano antistatic agents and inorganic nano antistatic agents and then adds them to the polyester layer. The antistatic film produced by this method has limitations: (1) The internal addition of inorganic nano antistatic agents is compatible with the film substrate, and the surface resistance of the film decreases to a limited extent, generally not less than 109Ω, so the antistatic effect and dispersibility are also average, and it affects the mechanical properties of the film;
[0005] Commonly used antistatic agents are divided into cationic, anionic and nonionic compounds and amphoteric polymers according to the surfactants used. These antistatic agents are small molecular weight compounds. Although they have good antistatic effects, they will reduce the thermal stability of plastics. Traditional antistatic materials such as carbon black and metal powders will inevitably cause problems such as poor high temperature stability, heat resistance and weather resistance of masterbatch.
[0006] Therefore, it is particularly important to improve the antistatic and thermal stability of masterbatch to meet the industry's requirements. Summary of the invention
[0007] The present invention aims to overcome the defects of poor antistatic effect and unsatisfactory thermal stability of masterbatches in the prior art, and to provide an antistatic PE film masterbatch and a preparation method thereof.
[0008] An antistatic PE film gray masterbatch includes the following raw materials in parts by weight: 70-90 parts of PE carrier resin, 5-15 parts of antistatic agent, 1-5 parts of titanium dioxide, 3-5 parts of carbon black, and 1-5 parts of zinc stearate. On the one hand, carbon black can be used as a color powder and mixed with titanium dioxide to form a gray color. On the other hand, carbon black cooperates with nano zinc oxide aluminum particles to reduce the risk of static electricity accumulation and further reduce the resistivity of the material from the inside of the masterbatch. In addition, carbon black can usually increase the hardness and strength of the material, and the addition of carbon black helps to improve the overall mechanical properties of the masterbatch. Among them, zinc stearate, as a dispersant, not only helps to reduce the agglomeration and adhesion of polyethylene, but also helps to stabilize the uniform dispersion of nano zinc oxide aluminum in the polyethylene masterbatch to avoid accumulation. The uniform dispersion of nano zinc oxide aluminum in the polyethylene masterbatch is an important factor in ensuring the continuity of the electron path, thereby improving the conductivity and antistatic ability.
[0009] Preferably, the antistatic agent is nano zinc oxide aluminum particles.
[0010] Preferably, the shape of the nano zinc-aluminum oxide particles is spherical. Spherical nano zinc-aluminum oxide particles are relatively regular in shape, and they form more contact points when they are tightly packed, which helps to form a more effective conductive path. In addition, spherical nano zinc-aluminum oxide particles usually have higher dispersibility, provide good dispersibility and uniformity, make it easier to form an orderly arrangement, and help to form a more effective conductive path.
[0011] Preferably, the particle size of the nano zinc oxide aluminum particles is 30-50nm. This is because smaller particles have a higher specific surface area, and a higher specific surface area means that the particle surface area is larger, and there is more surface area available for the formation of conductive channels, which generally helps to improve conductivity. In addition. Small-sized particles generally fill gaps better and provide more contact points, so electrons have more opportunities to transfer between particles, making it easier to achieve a continuous electron conduction path. It should be noted that smaller particle sizes may cause the particles to be too close together, increase the resistance of the electron tunnel, and thus reduce the conductive performance. Therefore, when the particle size of the nano zinc oxide aluminum particles is determined to be 30-50nm, the conductive effect is best.
[0012] The present invention also provides a method for preparing an antistatic PE film gray masterbatch, comprising the following steps: (1) weighing 70-90 parts of PE carrier resin, 5-15 parts of antistatic agent, 1-5 parts of titanium dioxide, 3-5 parts of carbon black, and 1-5 parts of zinc stearate by weight; (2) mixing and stirring the PE carrier resin, antistatic agent, titanium dioxide, carbon black, and zinc stearate weighed in step (1) in a mixer until uniform; (3) first placing the stirred mixture in an ultrasonic wave for vibration, and then placing it in an extruder, and finally preparing the antistatic PE film gray masterbatch through melt blending and extrusion. After the stirred mixture in step (3) is vibrated in an ultrasonic wave, the mixture is prevented from agglomerating, the uniformity of the mixture is improved, and the uniform distribution of the mixture is ensured, thereby improving the dispersibility, reducing the resistance of the mixture, and helping to improve the conductivity of the masterbatch.
[0013] Preferably, the ultrasonic oscillation time in step (3) is 2-3 hours.
[0014] Preferably, the extruder is a twin-screw extruder with a rotation speed of 200-230 r / min. If the rotation speed of the extruder is too high, it may cause excessive mechanical shearing, which may affect the uneven quality of the masterbatch.
[0015] Preferably, the extrusion temperature of the extruder is 140-150°C. The temperature of the extruder also has an important influence on the conductivity of the masterbatch. Generally, increasing the extrusion temperature helps to reduce the viscosity of the material, making the material easier to extrude. However, for the masterbatch, high temperature may cause thermal decomposition or cause structural changes in the material, thereby reducing the conductivity. Therefore, the extrusion temperature of the extruder is 140-150°C, which is the data obtained through experimental optimization.
[0016] By adopting the above technology, compared with the prior art, the beneficial effects of the present invention are as follows:
[0017] (1) The masterbatch prepared by the present invention has good antistatic effect. First, at the nanoscale, the electron mobility of zinc-aluminum oxide particles is relatively high, which leads to good conductivity of nano zinc-aluminum oxide. Secondly, the antistatic agent used is spherical nano zinc-aluminum oxide particles with a particle size of 30-50nm, which greatly improves the antistatic ability. In addition, the use of carbon black and the nano zinc-aluminum oxide particles can reduce the risk of static electricity accumulation, further reduce the resistivity of the material from the inside of the masterbatch, and greatly improve the antistatic performance. In addition, the antistatic ability is also inseparable from the assistance of zinc stearate and ultrasound. Zinc stearate, as a dispersant, not only helps to reduce the agglomeration and adhesion of polyethylene, but also helps to stabilize the uniform dispersion of nano zinc-aluminum oxide in polyethylene masterbatch to avoid accumulation. Improving the dispersion uniformity of the mixture under the action of ultrasound, the uniform dispersion of nano zinc-aluminum oxide in PE resin is an important factor to ensure the continuity of the electron path, which is conducive to improving the conductivity and antistatic ability. Therefore, the mutual cooperation of spherical nano zinc-aluminum oxide particles, carbon black, zinc stearate, and ultrasound, together perfectly help to greatly improve the antistatic ability of the masterbatch.
[0018] (2) The preparation process of the present invention is simple, the production efficiency is high, the material cost is low, and the application range is wide.
[0019] (3) Traditional antistatic film materials such as carbon black and metal powder inevitably cause poor high temperature stability of masterbatch, which in turn leads to poor heat resistance and weather resistance color difference performance. However, nano zinc oxide aluminum particles have extremely strong high temperature stability and high heat resistance. At the same time, they can effectively shield near infrared rays and reduce infrared emissivity, which can better solve the problems of heat resistance and weather resistance color difference performance. Therefore, the preparation of antistatic PE film gray masterbatch greatly exerts the advantages of masterbatch, with good antistatic performance, high heat resistance, good dispersibility, and good weather resistance color difference performance.
[0020] (4) Through the action of zinc stearate and ultrasound, the dispersion uniformity of the mixture is improved, and the antistatic ability of the masterbatch is further improved. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. Nano zinc oxide aluminum particles were purchased from Xuancheng Jingrui New Materials Co., Ltd., model VK-J50L. Other reagents used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0022] Example 1
[0023] An antistatic PE film grey masterbatch comprises the following raw materials in parts by weight: 70 parts of PE carrier resin, 5 parts of spherical nano zinc aluminum oxide particles with a particle size of 30 nm, 1 part of titanium dioxide, 3 parts of carbon black, and 1 part of zinc stearate.
[0024] The invention discloses a method for preparing an antistatic PE film gray masterbatch, comprising the following steps: (1) weighing 70 parts of a PE carrier resin, 5 parts of nano zinc oxide aluminum particles, 1 part of titanium dioxide, 3 parts of carbon black, and 1 part of zinc stearate by weight; (2) mixing and stirring the PE carrier resin, nano zinc oxide aluminum particles, titanium dioxide, carbon black, and zinc stearate weighed in step (1) in a mixer until they are uniform; (3) first placing the stirred mixture in an ultrasonic wave for 2 hours, and then placing it in a twin-screw extruder with a rotation speed of 200 r / min and an extrusion temperature of 140°C, and finally preparing an antistatic PE film gray masterbatch by melt blending and extrusion.
[0025] Example 2
[0026] An antistatic PE film grey masterbatch comprises the following raw materials in parts by weight: 80 parts of PE carrier resin, 10 parts of spherical nano zinc oxide aluminum particles with a particle size of 40 nm, 3 parts of titanium dioxide, 4 parts of carbon black, and 3 parts of zinc stearate.
[0027] The preparation method of antistatic PE film gray masterbatch comprises the following steps: (1) weighing 80 parts of PE carrier resin, 10 parts of nano zinc oxide aluminum particles, 3 parts of titanium dioxide, 4 parts of carbon black, and 3 parts of zinc stearate by weight; (2) mixing and stirring the PE carrier resin, nano zinc oxide aluminum particles, titanium dioxide, carbon black, and zinc stearate weighed in step (1) in a mixer until they are uniform; (3) first placing the stirred mixture in an ultrasonic vibration for 2.5 hours, and then putting it into a twin-screw extruder with a rotation speed of 250 r / min and an extrusion temperature of 145°C, and finally preparing the antistatic PE film gray masterbatch through melt blending and extrusion.
[0028] Example 3
[0029] An antistatic PE film grey masterbatch comprises the following raw materials in parts by weight: 90 parts of PE carrier resin, 15 parts of spherical nano zinc aluminum oxide particles with a particle size of 50 nm, 5 parts of titanium dioxide, 5 parts of carbon black and 5 parts of zinc stearate.
[0030] The preparation method of antistatic PE film gray masterbatch comprises the following steps: (1) weighing 90 parts of PE carrier resin, 15 parts of antistatic agent, 5 parts of titanium dioxide, 5 parts of carbon black, and 5 parts of zinc stearate by weight;
[0031] (2) Weighing the PE carrier resin, nano zinc oxide aluminum particles, titanium dioxide, carbon black, and zinc stearate prepared in step (1) and mixing them in a mixer until they are uniform; (3) The stirred mixture is first placed in an ultrasonic oscillation for 3 hours, and then placed in a twin-screw extruder at a speed of 230 r / min and an extrusion temperature of 150° C., and then melt-blended and extruded to finally obtain an antistatic PE film gray masterbatch.
[0032] Comparative Example 1
[0033] The difference between this comparative example and Example 1 is that 5 parts of spherical nano zinc oxide aluminum particles with a particle size of 30 nm are removed, and the other components and weight proportions of the antistatic PE film gray masterbatch and the preparation method of the antistatic PE film gray masterbatch are the same as those in Example 1.
[0034] Comparative Example 2
[0035] The difference between this comparative example and Example 1 is that 5 parts of spherical nano zinc oxide aluminum particles with a particle size of 30 nm are replaced by 5 parts of spherical nano zinc oxide aluminum particles with a particle size of 3 μm, and the other components of the antistatic PE film gray masterbatch and their weight proportions, and the preparation method of the antistatic PE film gray masterbatch are the same as those in Example 1.
[0036] Comparative Example 3
[0037] The difference between this comparative example and Example 1 is that 5 parts of spherical nano zinc oxide aluminum particles with a particle size of 30 nm are replaced by 5 parts of spherical nano zinc oxide aluminum particles with a particle size of 60 nm, and the other components of the antistatic PE film gray masterbatch and their weight proportions, and the preparation method of the antistatic PE film gray masterbatch are the same as those in Example 1.
[0038] Comparative Example 4
[0039] The difference between this comparative example and Example 1 is that 5 parts of spherical nano zinc oxide aluminum particles with a particle size of 30 nm are replaced by 5 parts of hexagonal wurtzite structure nano zinc oxide aluminum particles with a particle size of 30 nm, and the other components of the antistatic PE film gray masterbatch and their weight proportions, and the preparation method of the antistatic PE film gray masterbatch are the same as those in Example 1.
[0040] Comparative Example 5
[0041] The difference between this comparative example and Example 1 is that 5 parts of spherical nano zinc oxide aluminum particles with a particle size of 30 nm are replaced by 5 parts of spherical nano zinc oxide particles with a particle size of 30 nm, and the other ingredients and the preparation method of the masterbatch are the same as those in Example 1.
[0042] Comparative Example 6
[0043] The difference between this comparative example and Example 1 is that 3 parts of carbon black are removed, and the other components and weight proportions of the antistatic PE film gray masterbatch and the preparation method of the antistatic PE film gray masterbatch are the same as those in Example 1.
[0044] Comparative Example 7
[0045] The difference between this comparative example and Example 1 is that 1 part of zinc stearate is removed, and the other components and weight proportions of the antistatic PE film gray masterbatch and the preparation method of the antistatic PE film gray masterbatch are the same as those in Example 1.
[0046] Comparative Example 8
[0047] The difference between this comparative example and Example 1 is that the mixed material after stirring in step (3) of the preparation method of antistatic PE film gray masterbatch is put into a twin-screw extruder with a rotation speed of 200r / min and an extrusion temperature of 140°C, and finally the antistatic PE film gray masterbatch is obtained by melt blending and extrusion. That is, the step of "first placing in ultrasonic vibration for 2h" in step (3) is removed in this example, and the components and weight fractions of the antistatic PE film gray masterbatch and the other steps of the preparation method of the antistatic PE film gray masterbatch are the same as those in Example 1.
[0048] Performance Testing
[0049] The antistatic PE film gray masterbatch prepared in Examples 1-3 of the present invention and Comparative Examples 1-8 was tested for heat resistance and antistatic performance. The specific test results are shown in Table 1 below:
[0050] Table 1 Performance test of antistatic PE film gray masterbatch prepared in Examples 1-3 and Comparative Examples 1-8
[0051]
[0052]
[0053] As can be seen from Table 1 above, the antistatic PE film gray masterbatch prepared in the embodiment of the present invention is superior to the comparative example in terms of heat resistance, surface resistivity, dispersibility, and weather resistance color difference, indicating that the antistatic PE film gray masterbatch prepared in the embodiment of the present invention has high heat resistance, excellent antistatic property, good dispersibility, and good weather resistance color difference. Comparative Example 1 and Comparative Example 5 do not use nano zinc oxide aluminum particles, so the antistatic performance, heat resistance, and weather resistance color difference of the prepared antistatic PE film gray masterbatch are obviously the worst; Comparative Examples 2-4 do not use spherical nano zinc oxide aluminum particles with a particle size of 30-50nm, so the antistatic performance, heat resistance, and weather resistance color difference of the prepared antistatic PE film gray masterbatch are obviously poor; Comparative Example 6 does not use carbon black, resulting in good heat resistance and weather resistance color difference performance of the masterbatch, but slightly poor antistatic performance. This is because the lack of carbon black and nano zinc oxide aluminum particles increases the risk of static electricity accumulation and reduces the antistatic performance of the antistatic PE film gray masterbatch; compared with Examples 1-3, the antistatic performance of Comparative Examples 7-8 is poor. This is because Comparative Examples 7-8 do not add dispersant zinc stearate or perform ultrasonic treatment, resulting in the worst dispersibility of the masterbatch. Due to the uneven dispersion of the mixture, polyethylene will agglomerate and stick together, interrupting the continuity of the conductive electron path, thereby reducing the antistatic ability of the masterbatch.
[0054] In summary, the gray masterbatch for preparing antistatic PE film of the present invention has strong comprehensive performance, good antistatic performance, high heat resistance, good dispersibility and good weather resistance and color difference performance.
[0055] The above are only some embodiments of the present invention, and do not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are within the scope of the technical solution of the present invention.
Claims
1. An antistatic PE film grey masterbatch, Features: The invention comprises the following raw materials in parts by weight: 70-90 parts of PE carrier resin, 5-15 parts of antistatic agent, 1-5 parts of titanium dioxide, 3-5 parts of carbon black and 1-5 parts of zinc stearate, wherein the antistatic agent is nano zinc oxide aluminum particles, the nano zinc oxide aluminum particles are spherical in shape and the particle size of the nano zinc oxide aluminum particles is 30-50nm. The preparation method of the antistatic PE film gray masterbatch comprises the following steps: (1) weighing 70-90 parts of PE carrier resin, 5-15 parts of antistatic agent, 1-5 parts of titanium dioxide, 3-5 parts of carbon black and 1-5 parts of zinc stearate in parts by weight; (2) mixing and stirring the PE carrier resin, antistatic agent, titanium dioxide, carbon black and zinc stearate weighed in step (1) in a mixer until they are uniform; (3) first placing the stirred mixture in an ultrasonic wave for vibration, then putting it into an extruder, and extruding it through melt blending to finally prepare the antistatic PE film gray masterbatch.
2. The antistatic PE film gray masterbatch according to claim 1, Features: The ultrasonic oscillation time in step (3) is 2-3 hours.
3. The antistatic PE film gray masterbatch according to claim 1, Features: The extruder is a twin-screw extruder with a rotation speed of 200-230 r / min.
4. The antistatic PE film gray masterbatch according to claim 1, Features: The extrusion temperature of the extruder is 140-150°C.
Citation Information
Patent Citations
High-conductivity aluminum-doping zinc oxide nanometer noodles powder and preparation thereof
CN101274775A
Ageing-resistant building external wall thermal-insulation coating
CN108003675A
